Igualdade e proibição de discriminação no direito privado - Flores, Vinícius Letti (2014)
This research aimed to investigate the relationship between equality and private law. For this purpose, the study begins by analyzing the several dimensions of equality some of which were historically determined , namely: (i) equality as the prevalence of law, (ii) equality as the prohibition of arbitrariness, (iii) equality as the prohibition of discrimination, and, finally, (iv) equality as equality of opportunities, concluding that the material content of equality if not the only at least the most important is the prohibition of discrimination, which is a concept that, in addition to having constitutional support, should be understood as the prohibition of subjugation (antisubordination). Subsequently, the present study investigated how the efficacy of the fundamental rights works, particularly the right of equality, with regard to the public (legislative, executive, and judicial) powers and private actors, discussing the main theories proposed to explain the Drittwirkung, especially whether the bond is direct (actors act with a legitimate subjective right) or indirect (depending on state mediation), concluding that this efficacy has a direct effect, although it is a subsidiary and a prima facie right, i.e., the preference to accommodate the fundamental rights in private issues lies with the legislator and fundamental rights admit balancing, and that, once the occurrence of a discriminatory conduct is established, there is a prima facie precedence of equality as the prohibition of discrimination over any other principle or constitutionally protected right. Finally, this research analyzes three paradigmatic situations involving equality and private law, namely (i) contractual autonomy and the obligation of signing a consumer contract, (ii) testamentary autonomy and the differentiation between legitimate and illegitimate children, and (iii) the freedom of religious speech with regard to sexual orientation.